Prototype of Corn Thresher Unit for Corn Combine Harvester - Diang Sagita; Radite Praeko Agus Setiawan; Wawan Hermawan (The University of Lampung, 2019)
One of the ways to support corn production is through technology implementation, but the domestic industries have not attempted to produce technology for harvesting activities especially corn harvesting. This research was carried out to get the best design, prototype and performance of corn thresher unit to be applied to the design of a corn combine harvester. The components consist of threshing cylinders, perforated cages, grain screw conveyors and corn cob entry holes. The research method begins from analyzing (functional and structural designs), designing, testing performance, evaluating and modifying. The performance test was carried out stationary using corn cob raw material. The performance of the thresher unit has been quite good. The results show that the best performance was the prototype with the last modification (C). Threshing efficiency reached 93.75%, percentage of un-threshed kernel was 6.25%, and cleanliness level 90.68%. While threshing capacity was 358.28 kg/hour, which corn cob feeding was carried out by humans with a feeding capacity of 420.05 kg/hour